Análisis jurídico para reformar el art. innumerado 5 del código orgánico de la niñez y adolescencia, a fin de garantizar el derecho de los niños, niñas, y adolecentes, que no poseen padres u obligados subsidiarios frente al derecho de alimentos - Guapulema Galarza, Clever Victoriano (2015)
Within this thesis entitled "LEGAL ANALYSIS TO REFORM THE ART. Unnumbered 5 Professional Code for Children and Adolescents, TO ENSURE THE RIGHT OF CHILDREN AND TEENS, who do not have parents or forced SUBSIDIARY FOOD RIGHT FRONT ""circumscribed of family rights in which food is part of the child or adolescent, who is fundamental for the development of the same are currently in the best interests guaranteed by the Constitution of the Republic of Ecuador, have no legal mechanisms when children and adolescents have not joint obligors. Just as is necessary to fulfill the rights of children in our society Ecuadorian especially the right to food to meet their basic needs and basic, the law provides to family rights or guarantees for their development. As we know there are legal factors such as parental rights, the exercise only parents, as given custody of the child in the divorce, possession is when the judge gives judgment, showing that Parents are unworthy of possessing custody. Similarly there is the solidarity of the same food that has been extended to relatives in direct line and collateral. The Ecuadorian children need the support of state institutions the same as currently play a key role in the fulfillment of the interests of children and adolescents-especially within their integral development, which have the same right. So it is necessary to create the right conditions for children to receive food affinity.The state is the only guarantee of the administration of justice through the rule of law. Inside this issue raised is necessary to implement laws and mechanisms to ensure the best interests of the child or adolescent. Faced with providing food, in solidarity.Today our state has adopted, solidarity regarding food which seeks to give them blood relatives, children and adolescents always when principals cannot do so, therefore, the interests of the child is based not only on food but on providing comprehensive protection for their moral and material. But what happens when there is not obligated subsidiary. This thesis aims to ensure the rights of children and adolescents, in solidarity alimony benefit, since in many cases the parents are responsible, not for the care and worst of his integral development today The State guarantees the rights and interests of children, so it is the duty of the State to implement legal mechanisms to fulfill the rights of children, the same that come before any other fees that violate the moral and material thereof